Volume 8: Energy Systems: Analysis, Thermodynamics and Sustainability; Sustainable Products and Processes 2008
DOI: 10.1115/imece2008-67563
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Residential Thermal Control With Wireless Sensor Networks: A Case Study for Air Conditioning in California

Abstract: Residential thermostats are sensor-limited devices, but low-cost wireless sensor network technology is enabling new spatially distributed sensing capabilities. This paper evaluates the energy and comfort performance of three multi-sensor control strategies that use wireless temperature and humidity sensors in each room and that can be applied to existing on-off residential central systems. The multi-sensor control strategies adjust the temperature set point of a thermostat to control the average of all room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Predicting yearly energy savings from the test results is therefore risky. Comparison of the results in (Ota et al 2008) and (Siemann 2010) provides a cautionary tale. Based on experimental evaluation of a few days (3 to 6), up to 79% energy-savings potential of a wireless sensor-based home HVAC system was reported in (Ota et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Predicting yearly energy savings from the test results is therefore risky. Comparison of the results in (Ota et al 2008) and (Siemann 2010) provides a cautionary tale. Based on experimental evaluation of a few days (3 to 6), up to 79% energy-savings potential of a wireless sensor-based home HVAC system was reported in (Ota et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Comparison of the results in (Ota et al 2008) and (Siemann 2010) provides a cautionary tale. Based on experimental evaluation of a few days (3 to 6), up to 79% energy-savings potential of a wireless sensor-based home HVAC system was reported in (Ota et al 2008). Upon deploying the system in a home in a different climate zone and collecting data for more than a month, it was found that the energy consumption after the retrofit was statistically either worse or indistinguishable from that of before the retrofit (Siemann 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Their control strategy involved turning off the AC in unoccupied zones and manipulating the set-point temperature. A multi-sensor non-learning control strategy has been proposed in [18]. This paper evaluates the energy and comfort performance of three multi-sensor control strategies that use wireless temperature and humidity sensors and that can be applied to existing ON/OFF central HVAC system.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies [2][3][4] had been done in the United States on finding an optimum way of reducing energy consumption of HVAC system. Concept that had been studied are by improving area temperature reading method and feedback to air conditioner unit or proper prediction of heat rejection by occupancy or external heat radian.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also looked into other types of refrigerant that have potential to reduce HVAC power consumption [5]. Most of the studies we have come across have been done by using mathematical simulation approach except [4] which had done by actual on-site study in California, United States. A study has been done in Germany that showed of high energy saving potential based on consumer behaviour in a university building [6].…”
Section: Introductionmentioning
confidence: 99%